Impact of Differentiated Learning Management on Enhancing Students' Creative Thinking in Mathematics - Laili, Azmil; Istikomah, Istikomah (AL-ISHLAH: Jurnal Pendidikan, 2024)
In the era of globalization, innovation in education is essential, particularly in fostering students' creative thinking abilities. Mathematics, as a core subject, requires teaching strategies that stimulate creativity. This study explores the influence of differentiated learning management in mathematics on students' creative thinking at MIN 1 Sidoarjo. A quasi-experimental design with a quantitative approach was used. The research population included all students at MIN 1 Sidoarjo, with the sample drawn from class VI students. Data were collected using pre-tests, post-tests, and questionnaires, and analyzed using t-tests to assess the impact of the differentiated learning approach on creative thinking. The findings reveal that differentiated learning management significantly enhances students' creative thinking in mathematics. The experimental group, which received differentiated instruction, showed greater improvements in creative thinking compared to the control group, which followed a traditional teaching approach. The results highlight the positive influence of differentiated learning strategies in promoting creativity within mathematics education. The experimental group's superior performance underscores the need for more innovative teaching practices to meet the demands of modern education. Differentiated learning management in mathematics has a significant positive effect on students' creative thinking. These findings offer important insights for educators seeking to enhance creativity through tailored instructional methods.